1997
DOI: 10.1007/s002280050245
|View full text |Cite
|
Sign up to set email alerts
|

Age-dependent differences in the anticoagulant effect of phenprocoumon in patients after heart valve surgery

Abstract: Older patients (> 70 years) require a dose approximately 30% lower than younger patients (< 160 years). Pharmacokinetic reasons (reduced metabolic clearance) are mainly responsible for the lower dose requirement of the older patients after heart valve surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…These results agree with the findings of recent studies in which the risk of life-threatening or fatal bleeding was significantly higher in older than younger patients receiving OAT. 6,16 In this study, all fatal bleeding events recorded in both groups were intracranial hemorrhages. Others have also reported that the risk of intracranial bleeding during OAT is higher in older persons.…”
Section: Commentmentioning
confidence: 57%
“…These results agree with the findings of recent studies in which the risk of life-threatening or fatal bleeding was significantly higher in older than younger patients receiving OAT. 6,16 In this study, all fatal bleeding events recorded in both groups were intracranial hemorrhages. Others have also reported that the risk of intracranial bleeding during OAT is higher in older persons.…”
Section: Commentmentioning
confidence: 57%
“…3335,38 We believe that these age-related imbalances in hemostatic protein regulation and production by VECs are not likely to cause spontaneous development of thrombus. However, when injury or insult occur at the valve endothelium, the aging-induced imbalance in the expression of anti-thrombotic and thrombotic proteins by VECs will lower the VEC's capability to maintain hemostasis; thus causes AV tissues to be more susceptible to thrombotic complications.…”
Section: Discussionmentioning
confidence: 92%
“…This phenomenon is consistent with clinical reports that elderly patients require lower doses of anti-coagulants after heart valve surgeries than do adult patients, due to lower clearance kinetics of the drugs and decreased clotting ability in elderly patients. 38 …”
Section: Discussionmentioning
confidence: 99%
“…The average INR result was nearly identical in the various age groups, but the average dose decreased with age whereas the instability index increased. It has been previously shown that steady‐state warfarin doses decrease with age and that this is mainly due to a significantly reduced metabolic clearance in the elderly (Russmann et al , 1997). A reduced metabolic clearance, resulting in a narrow therapeutic range, might also explain both the increased individual variable response to treatment in the elderly, and the observed association between the minimum INR value and the likelihood of over‐anticoagulation.…”
Section: Discussionmentioning
confidence: 99%